Application of SMA spring tendons for improved grasping performance. (1st February 2019) - Lee, Ji-Hyeong; Chung, Yoon Seop; Rodrigue, Hugo
Abstract: Shape memory alloy (SMA)-based soft actuators and grippers have generally used SMA wires due to design restrictions, limited actuation force and poor cooling performance of SMA springs. This work demonstrates that SMA springs can be used for high performance soft actuation by positioning them externally as a tendon with the force transmitted to the polymeric matrix using a tendon. Through improvements by using active cooling through fans, a spring longer than the matrix and a matrix with a trapezoidal cross-section, the actuator was capable of cyclic actuation at 0.25 Hz, a bending angle of 270° and a tip force of 0.21 N. The same actuator design was used to build a soft robotic gripper capable of grasping objects with a wide range of shapes and weights, and its maximum pull-off force was measured to be 30 N. The gripper was also capable of holding a weight of 2 kg. The increased design freedom of the proposed design would also enable further improvements to the bending and grasping performance of the actuator, and the use of SMA-based soft actuation to more complex designs and a wider range of robotic applications.